THE URGENCY OF WOMEN'S LEADERSHIP IN THE BUDGET FORMULATION: ISLAMIC FINANCE PERSPECTIVE - Luqmanul Hakiem Ajuna (Finansha: Journal of Sharia Financial Management, 2023)
Although only four out of thirty-five regional apparatus organizations are led by women, women's participation in the regional revenue and expenditure budget in Gorontalo City has been so great. This can be seen in the strategic position in development budgeting and regional financial planning led by a woman. Therefore, in this study, researchers want to know and understand how the urgency of women leaders in government budgeting. This research is a qualitative research with a phenomenological approach that is presented descriptively analytically and coupled with thematic studies of Islamic finance. The research location chosen is Gorontalo, which is nicknamed Serambi Madinah. The results showed that the choice of women to lead the regional planning, research and development agency is a proof of the existence of women in budgeting. The policy has provided space to voice the budget in favor of women themselves. In addition, the four female leaders who became the object of research succeeded in applying Islamic financial values in managing the regional budget, namely transparency (Siddiq) and accountability (Amanah). While in its dual function Islam does not prohibit women from appearing as leaders, but still pay attention to Islamic teachings and do not leave their main role in household affairs.